Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To simplify the expression [tex]\((2 + j s)^2 + \frac{5(7 + j 2)}{3 - j 4} - j (4 - j 6)\)[/tex] and express it in the form [tex]\(a + j b\)[/tex], follow these steps:
### Step-by-Step Solution
1. Simplify [tex]\((2 + j s)^2\)[/tex]:
[tex]\[ (2 + j s)^2 = (2 + j s)(2 + j s) \][/tex]
Using the distributive property:
[tex]\[ = 2(2) + 2(j s) + (j s)(2) + (j s)(j s) \][/tex]
Recall that [tex]\(j^2 = -1\)[/tex]:
[tex]\[ = 4 + 2j s + 2j s + j^2 s^2 \][/tex]
[tex]\[ = 4 + 4j s - s^2 \][/tex]
2. Simplify [tex]\(\frac{5(7 + j 2)}{3 - j 4}\)[/tex]:
Let's denote the numerator as [tex]\(5(7 + j 2)\)[/tex] and the denominator as [tex]\(3 - j 4\)[/tex]:
[tex]\[ 5(7 + j 2) = 35 + 10j \][/tex]
To handle the division by a complex number, we multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{35 + 10j}{3 - j 4} \cdot \frac{3 + j 4}{3 + j 4} \][/tex]
The denominator becomes:
[tex]\[ (3 - j 4)(3 + j 4) = 9 + 12j - 12j - 16j^2 = 9 + 16 = 25 \][/tex]
And the numerator:
[tex]\[ (35 + 10j)(3 + j 4) = 35 \cdot 3 + 35 \cdot j 4 + 10j \cdot 3 + 10j \cdot j 4 \][/tex]
[tex]\[ = 105 + 140j + 30j - 40 = 65 + 170j \][/tex]
Combining:
[tex]\[ \frac{65 + 170j}{25} = \frac{65}{25} + j \frac{170}{25} = \frac{13}{5} + j \frac{34}{5} \][/tex]
3. Simplify [tex]\(-j (4 - j 6)\)[/tex]:
[tex]\[ -j (4 - j 6) = -j \cdot 4 + j^2 \cdot 6 \][/tex]
Recall that [tex]\(j^2 = -1\)[/tex]:
[tex]\[ = -4j + 6(-1) = -4j - 6 \][/tex]
4. Combine all parts:
Now combining all the simplified parts:
[tex]\[ (4 + 4j s - s^2) + \left( \frac{13}{5} + j \frac{34}{5} \right) - (6 + 4j) \][/tex]
Group the real parts and the imaginary parts together:
[tex]\[ \left(4 + \frac{13}{5} - 6 - s^2\right) + \left(4j s + j \frac{34}{5} - 4j\right) \][/tex]
Simplify the real and imaginary parts:
[tex]\[ 4 - 6 + \frac{13}{5} = -2 + \frac{13}{5} = -2 + 2.6 = 0.6 = \frac{3}{5} \][/tex]
[tex]\[ 4j s + j \frac{34}{5} - 4j = j \left(4 s + \frac{34}{5} - 4\right) = j \left(4 s + \frac{34 - 20}{5}\right) = j \left(4 s + \frac{14}{5}\right) \][/tex]
5. Write the simplified expression:
Combine these results:
[tex]\[ -s^2 + \frac{3}{5} + j \left(4 s + \frac{14}{5}\right) \][/tex]
Thus, the simplified form of the expression is:
[tex]\[ a + j b = -s^2 + \frac{3}{5} + j \left(4 s + \frac{14}{5}\right) \][/tex]
Or separating real and imaginary parts clearly:
- Real part: [tex]\( \boxed{-s^2 + \frac{3}{5}} \)[/tex]
- Imaginary part: [tex]\( \boxed{4 s + \frac{14}{5}} \)[/tex]
### Step-by-Step Solution
1. Simplify [tex]\((2 + j s)^2\)[/tex]:
[tex]\[ (2 + j s)^2 = (2 + j s)(2 + j s) \][/tex]
Using the distributive property:
[tex]\[ = 2(2) + 2(j s) + (j s)(2) + (j s)(j s) \][/tex]
Recall that [tex]\(j^2 = -1\)[/tex]:
[tex]\[ = 4 + 2j s + 2j s + j^2 s^2 \][/tex]
[tex]\[ = 4 + 4j s - s^2 \][/tex]
2. Simplify [tex]\(\frac{5(7 + j 2)}{3 - j 4}\)[/tex]:
Let's denote the numerator as [tex]\(5(7 + j 2)\)[/tex] and the denominator as [tex]\(3 - j 4\)[/tex]:
[tex]\[ 5(7 + j 2) = 35 + 10j \][/tex]
To handle the division by a complex number, we multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{35 + 10j}{3 - j 4} \cdot \frac{3 + j 4}{3 + j 4} \][/tex]
The denominator becomes:
[tex]\[ (3 - j 4)(3 + j 4) = 9 + 12j - 12j - 16j^2 = 9 + 16 = 25 \][/tex]
And the numerator:
[tex]\[ (35 + 10j)(3 + j 4) = 35 \cdot 3 + 35 \cdot j 4 + 10j \cdot 3 + 10j \cdot j 4 \][/tex]
[tex]\[ = 105 + 140j + 30j - 40 = 65 + 170j \][/tex]
Combining:
[tex]\[ \frac{65 + 170j}{25} = \frac{65}{25} + j \frac{170}{25} = \frac{13}{5} + j \frac{34}{5} \][/tex]
3. Simplify [tex]\(-j (4 - j 6)\)[/tex]:
[tex]\[ -j (4 - j 6) = -j \cdot 4 + j^2 \cdot 6 \][/tex]
Recall that [tex]\(j^2 = -1\)[/tex]:
[tex]\[ = -4j + 6(-1) = -4j - 6 \][/tex]
4. Combine all parts:
Now combining all the simplified parts:
[tex]\[ (4 + 4j s - s^2) + \left( \frac{13}{5} + j \frac{34}{5} \right) - (6 + 4j) \][/tex]
Group the real parts and the imaginary parts together:
[tex]\[ \left(4 + \frac{13}{5} - 6 - s^2\right) + \left(4j s + j \frac{34}{5} - 4j\right) \][/tex]
Simplify the real and imaginary parts:
[tex]\[ 4 - 6 + \frac{13}{5} = -2 + \frac{13}{5} = -2 + 2.6 = 0.6 = \frac{3}{5} \][/tex]
[tex]\[ 4j s + j \frac{34}{5} - 4j = j \left(4 s + \frac{34}{5} - 4\right) = j \left(4 s + \frac{34 - 20}{5}\right) = j \left(4 s + \frac{14}{5}\right) \][/tex]
5. Write the simplified expression:
Combine these results:
[tex]\[ -s^2 + \frac{3}{5} + j \left(4 s + \frac{14}{5}\right) \][/tex]
Thus, the simplified form of the expression is:
[tex]\[ a + j b = -s^2 + \frac{3}{5} + j \left(4 s + \frac{14}{5}\right) \][/tex]
Or separating real and imaginary parts clearly:
- Real part: [tex]\( \boxed{-s^2 + \frac{3}{5}} \)[/tex]
- Imaginary part: [tex]\( \boxed{4 s + \frac{14}{5}} \)[/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.